Storage Properties of the Shale Reservoir of the Lower Keluke Formation in the Shihuigou Area: Implications for the Controlling Factors - Liang Zhang (Geofluids)
In this study, the characteristics of shale gas reservoirs of the lower part of the Keluke Formation in the Shihuigou area were investigated by using thin sections, scanning electron microscopy (SEM), and isothermal adsorption, combined with geochemical experimental analysis. Consequently, the controlling factors of the adsorption capability and gas content of the studied shale reservoir are explored. The results show that the shale reservoir space of the Keluke Formation is dominated by pores and fractures. The pores are divided into intergranular pores, intragranular pores, and dissolved pores. The pore volume of medium pores is higher than that of micropores, but the specific surface area of the medium pores is lower than that of micropores. The pore size distribution of medium pores has a feature of single peak, while the distribution of micropores is multipeaked. The results of physical properties and field gas adsorption indicate that the reservoir quality and gas content of the lower part of the Keluke Formation are good. Meanwhile, the total organic content (TOC) has a positive relationship with the methane adsorption. However, the field gas adsorption does not have a clear relationship with TOC and methane adsorption, but a positive correlation with clay mineral content. Therefore, the present study concludes that the natural gas in the shale reservoir of the lower part of the Keluke Formation is predominantly accumulated in form of free gas, and the concentration of free gas is higher than that of the adsorbed gas.